Reducing Blood Bank workload through effective Remote Electronic Blood Issue - Auchinleck, Geoffrey F. (CMBES Proceedings, 2010)
Hospital blood banks are facing growing pressures due to increasing demand and a shortage of qualified blood bank techs. One response to this has been the use of Electronic Cross Matching of blood for patients, which allows blood to be directly issued for patients based on the patient’s blood tests and history. This has helped reduce workload, but the practice of ‘pre-allocating’ blood units prior to surgery means that most hospital blood banks crossmatch an average of two blood units for each unit actually transfused. Electronic release of blood admits the possibility of Remote Electronic Blood Issue, in which unallocated blood stocks are kept near the point of use and released “just in time”. We have combined Remote Electronic Blood Issue with computer controlled multi-compartment refrigerators to provide safe and effective “Blood Vending Machines”. This approach has reduced blood bank workloads by up to 52%, has reduced the amount of blood required in inventory, and has reduced the time required to provide blood from 20 minutes or more to about one minute. This system is now in use in several hospitals in the UK, US and Canada, and similar results have been seen in each case.